Understanding the dignity experience of South African patients in primary palliative care - Raksha Balbadhur; Elizabeth Gwyther (South African Family Practice)
Background: To meet the goals of primary palliative care for patients with advanced disease and to provide holistic patient-centred compassionate care that respects the experience of patients, dignity in its entirety needs to be understood from the patients’ perspective. There are no studies to understand the predominant factors that impact the dignity experience of South African patients with advanced disease.